Scrutinizing the chemical nature and photophysics of an expanded hemiporphyrazine: The special case of [30]trithia-2,3,5,10,12,13,15,20,22,23,25, 30-dodecaazahexaphyrin - Trukhina, Olga N.; Rodriguez-Morgade, M. Salome; Wolfrum, Silke; Caballero, Esmeralda; Snejko, Natalia; Danilova, Elena A.; Gutierrez-Puebla, Enrique; Islyaikin, Mikhail K.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
Thirty π-electron-expanded hemiporphyrazines 1a-c have been prepared by crossover condensation reaction of 2,5-diamino-1,3,4-thiadiazole and the corresponding phthalonitrile (3) or diiminoisoindoline (4) derivatives. The expanded azaporphyrin hexamers have been unequivocally characterized by means of spectroscopic, crystallographic, and electrochemical techniques. Weak intramolecular hydrogen bonding imposes a planar conformation to macrocycles. However, the overall electronic delocalization is low, and the nature of the resulting [30]heteroannulene is nonaromatic, as confirmed by NMR studies, XR diffraction analysis, and calculation of the NICS(0) value. Studies on a wide range of physicochemical features including ground, excited, reduced, and oxidized states provide evidence for the wide applicability of these 30 π-electron-expanded hemiporphyrazines in processes involving electron transfer. A key asset of our work is the systematic development of spectroscopic and kinetic markers for the formation and decay of all of the aforementioned species. Thirty π-electron-expanded hemiporphyrazines evolve as broadly absorbing light harvesters with excited state energies of around 2.3 eV that are susceptible to facile one-electron reduction and one-electron oxidation reactions. © 2010 American Chemical Society.